Utilizing LMS tools to help with student assessment in an online course - Turner, Dudley B. (EAI Endorsed Transactions on e-Learning, 2015)
In online learning, feedback to students is important in their progress. Assessments are often final or summative assessments that do not allow the student to adjust or improve their learning progress. Assessment, however, takes valuable time. This paper describes how using the tools available in a LMS can assist faculty in assessing student work and provide helpful feedback to students in an online course. The tools available for faculty to use can be set up to save time for the faculty during assessments. The assignments in this study were developed based on previous research indicating assessment can be an aid to student learning, and students who know how well they are doing can make needed adjustments. Students used the feedback from these LMS tools to decide whether or not to try again or move on. Students had the opportunity for multiple attempts at assignments and received feedback on each to help measure their learning. The rubric tool was used to not only grade student papers but also to provide appropriate feedback for student performance on the levels of achievement. Quizzes can be automatically graded. Any additional attempts are drawn from a bank of questions. Results from this pilot study show the benefits of multiple attempts at quizzes and assignments. Students who took advantage of multiple attempts did improve their scores. The paper also discusses further research that to help support this practice.
Keywords: online learning; assessment; LMS; rubrics; feedback